Anti-inflammatory effect of meloxicam on experimental vasospasm in the rat femoral artery - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2008)
Cerebral vasospasm influences morbidity and mortality following subarachnoid haemorrhage (SAH). Inflammation is believed to play a role in post-haemorrhagic vasospasm. Meloxicam is a non-steroidal anti-inflammatory drug. We investigated the effect of meloxicam on a rat femoral artery vasospasm model using the radial wall thickness and cross-sectional lumen area as parameters under light, scanning and transmission electron microscopy examination. Rats were randomly separated into SAH, SAH + meloxicam and control groups. Rats in the SAH + meloxicam group were given meloxicam at 2 mg/kg daily for 7 days. Femoral arteries were examined by light microscopy and scanning and transmission electron microscopy, and for morphometric analysis. A statistically significant difference (p < 0.001) was detected between the SAH and SAH + meloxicam groups. Meloxicam treatment reduced ultrastructural and morphometric vasospastic changes. These findings support the hypothesis that inflammation may play a role in the pathophysiologyical pathways of post-haemorrhagic cerebral vasospasm. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: cerebral vasospasm; femoral artery; inflammation; meloxicam; subarachnoid haemorrhage; EXPERIMENTAL SUBARACHNOID HEMORRHAGE; DELAYED CEREBRAL VASOSPASM; BASILAR ARTERY; MODEL; INFLAMMATION; INHIBITION; IBUPROFEN; CYCLOOXYGENASE-2; PROSTACYCLIN; PREVENTION